Sex expression & American women writers, 1860-1940 - Bauer, Dale M., 1956- (University of North Carolina Press, 2009)
American women novelists of the late nineteenth and early twentieth centuries registered a call for a new sexual freedom, Dale Bauer contends. By creating a lexicon of sex expression, many authors explored sexuality as part of a discourse about women's needs rather than confining it to the realm of sentiments, where it had been relegated (if broached at all) by earlier writers. This new rhetoric of sexuality enabled critical conversations about who had sex, when in life they had it, and how it signified. Whether liberating or repressive, sexuality became a potential force for female agency in.